Evaluasi Pelaksanaan Program Kampung Iklim di Empat Zonasi Pantai Provinsi Sulawesi Selatan - suciasih, indah; Asjulia, Asjulia; Syafar, Andi Abdul Rahman (Jurnal Eboni, 2024)
The research aims to evaluate the Climate Village Program (ProKlim) for the last 5 years in terms of distribution and the role of government and communities in four coastal zones of South Sulawesi Province. The research was conducted at the Sulawesi Regional Climate Change Control Center with the locus of four districts representing four coastal zones in South Sulawesi Province, namely Bone Regency, Bulukumba Regency, Gowa Regency and Maros Regency. The research lasts from August to October 2023. Researchers processed ProKlim location distribution data and distributed questionnaires to local government representatives and communities at ProKlim locations using Purposive Sampling. The method used is qualitative descriptive and data analysis with Likert Scale. The results showed that the distribution of ProKlim in South Sulawesi Province for the last 5 years (2018-2022) was the highest in 2022 with 71 locations and the least was in 2021 with 30 locations. The most ProKlim locations are in Bone Regency with 41 locations, Bulukumba Regency with 31 locations, Gowa Regency with 30 locations and Maros Regency with 29 locations. Based on research conducted regarding the role of local governments and communities in influencing Proklim, it is known that in the section local government representatives have an understanding of 83.53% which means they understand very well and in the section representatives of ProKlim locations are 79.73% who understand.